Thickened Retinal Nerve Fiber Layers Associated With High-Altitude Headache - Yin, Xianhong; Li, Yi; Ma, Yanyun; Xie, Yuan; Wang, Kun; Sun, Dayan; Liu, Xiaoyu; Hao, Meng; Liang, Meng; Zhang, Shixuan; Guo, Yuan; Jin, Li; et al. (Frontiers in Physiology, 2022)
Purpose: This study aimed to quantify the different quadrants of the optic nerve head (ONH) and macular parameters and their changes during exposure to high altitude, and to assess their correlation with high-altitude headache (HAH). Methods: Spectral-domain optical coherence tomography (OCT) was used to quantify changes in the retinal structure in 109 healthy subjects during acute exposure to high altitude (3,700 m). Self-reported symptoms of HAH and acute mountain sickness AMS were assessed using Lake Louise Score (LLS), alongside measurements of physiological parameters (oxygen saturation [SpO2], heart rate [HR], hemoglobin level [Hb], and red blood cell [RBC] count). Measurements were taken before and after exposure to the high-altitude environment. The correlations of these parameters and changes at ONH were examined. Results: With the exposure to high altitude, the incidence of AMS was 44.0% and the frequency of HAH was 67.0% (54.1% mild, 12.9% moderate-severe). As for systemic parameters measured at high altitude, the participants exhibited significantly lower SpO2, higher resting HR, higher Hb, and a higher RBC (all p < 0.05). Key stereometric parameters used to describe ONH [superior, inferior, nasal, temporal, and mean retinal nerve fiber layer (RNFL) thickness] and macula (macular thickness) increased at high altitude compared with baseline. Most parameters of ONH changed, especially superior, inferior, and mean RNFL thickness (p < 0.05). There was a significant correlation between the ratios of RNFL at ONH and HAH [mean thickness (r = 0.246, p = 0.01); inferior (r = 0.216, p = 0.02); nasal (r = 0.193, p = 0.04)]. No associations between parameters of ONH and AMS or LLS were observed. Conclusion: The high-altitude environment can increase RNFL thickness at ONH. Furthermore, we found that the ratios of mean thickness, inferior area, and nasal area correlated positively with HAH, which provides new insights for understanding of the underlying pathological mechanisms of high-altitude retinopathy (HAR).